The Analysis of Regional Expenditure Responses to Block Grants Transfer from Central Government - Ahmad Nawawi (Jurnal Anggaran dan Keuangan Negara Indonesia (AKURASI), 2021)
The implementation of fiscal decentralization in Indonesia is exactly two decades in year 2021, during this time the policies in the field of transfers to regions have developed with a significant increase in the budget. The budget increasing of transfer to regions is expected to increase the region in providing services to the community and increase development. Furthermore, the objectives of fiscal decentralization are to reduce fiscal gaps and encourage regional governments to be more independent. This study aims to determine the response or behavior of regional spending to transfer funds (block grants) from the central government. The research locus are all districts/cities in West Java, Central Java, and East Java Provinces and used a panel data equation, with variables are regional expenditure, general allocation fund (DAU), sharing allocation fund (DBH), and local revenues (PAD). The results showed that the block grant in the form of DAU encouraged an increase in regional spending. Meanwhile, DBH does not cause a flypaper effect. In the future, in order to achieve the region’s independence, the influence of the flypaper effect from the DAU should be minimized, and the exploration of potential regional revenues needs to be optimized.